Kompetisi Industri Transportasi: Tinjauan Komunikasi Pemasaran Jasa PT Kereta Api Indonesia - Prima Mulyasari Agustini (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2008)
The development of transportation industry has removed the train business from its monopolistic business. Sooner or later, the government will open up opportunity for private parties to participate in the train business. In order to successfully anticipate this future, PT Kereta Api Indonesia (KAI) needs to change its communication strategy. Integrated Service Marketing Communication (ISMC) was recommended as a strategic approach covering management of service promise, management of customer expectation, customer education improvement, and management of internal marketing communication.